2021
DOI: 10.1093/jas/skab264
|View full text |Cite
|
Sign up to set email alerts
|

β-Hydroxy β-methylbutyrate supplementation to adult Thoroughbred geldings increases type IIA fiber content in the gluteus medius

Abstract: Consumption of β-hydroxy β-methylbutyrate (HMB) alters muscle composition and metabolism leading to strength and agility improvements in human athletes. To determine if HMB affects athletic performance and muscle function in horses, Thoroughbred geldings were fed a control (CON; n=5) or HMB (n=6) supplement for 6 wks prior to completing a standardized exercise test (SET). Gluteus Medius (GM) muscle biopsies were obtained before the SET for fiber typing. Heart rate (HR), biceps femoris (BF) and semitendinosus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Until recently, several studies using surface electromyography (sEMG) have reported that the muscle activity during trotting increases with speed [1][2][3][4][5]. However, the effect of speed on muscle activity during canter and gallop [6], which are the gaits required in considerably high-intensity exercises (e.g., cross-country and horse racing), remains poorly known.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, several studies using surface electromyography (sEMG) have reported that the muscle activity during trotting increases with speed [1][2][3][4][5]. However, the effect of speed on muscle activity during canter and gallop [6], which are the gaits required in considerably high-intensity exercises (e.g., cross-country and horse racing), remains poorly known.…”
Section: Introductionmentioning
confidence: 99%